Refugee, Asylum Seeker and Immigrant Women Mental Health - Ayse Devrim Basterzi (Psikiyatride Güncel Yaklaşımlar, 2017)
Social situation, social networks, power relationships, socioeconomic conditions, education and physical environment of people affect to encounter with trauma and disasters. These social factors also have an effect on traumatized people’s mental health. Gender roles are affected these entire social context and mental disorders. War and migration frequently lead to increasing inequality between men and women. This article reviews the studies about refugee, asylum seeker and immigrant’s women mental health and gender roles. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2017; 9(4.000): 379-387]